Corporate Zakat in Perspective of Stakeholder Theory: A Case Study of Islamic Rural Banks - Riduwan Riduwan; Hamim Ilyas; Mufti Alam Adha (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
In Indonesia, potential sources of zakat are grouped into three parts: potential zakat from individual or family groups, potential zakat from companies/industry, and from the results of deposits of zakat funds stored in banks. This study analyzes corporate zakat from the stakeholder theory's perspective with primary and secondary data from Islamic rural banks in the Special Region of Yogyakarta. The data analysis used qualitative from interviews and quantitative descriptive approach from the company report. Conclusions are drawn by describing secondary data, which is deepened through interviews with the directors of Islamic rural banks and relating them to stakeholder theory. The results of this study indicate that corporate zakat is in line with stakeholder theory because it positively impacts the performance of Islamic rural banks in Yogyakarta. Meanwhile, the muamalah approach to corporate zakat law has opened space for ijtihad against zakat law. Another conclusion states that Islamic rural banks that run zakat will improve business performance because the social approach can maintain stronger business relationships.